DEVELOPMENT OF MANAGEMENT STAFF OF THE ORGANIZATION IN A KNOWLEDGE ECONOMY - VEDERNIKOV, MYKHAILO; BAZALIYSKA, NATALIYA; VOLIANSKA-SAVCHUK, LESIA; ZELENA, MARIA; CHERNUSHKINA, OKSANA; KOSHONKO, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Features of labor management in modern conditions are re-searched  in  the  article.  Directions  of  improving  management system activities are determined. Methodological approaches to the formation of the system of development of management personnel of the organization in the conditions of knowledge economy are considered. The stages of development of the information society in connection with the innovative phase of development of the knowledge economy are described. Theoretical approaches to the definition of "knowledge economy" are formed. The characteristic features of the "knowledge economy" are highlighted. The stages of implementation of the process of increasing the efficiency of development of the management staff of the organization in the conditions of knowledge economy are offered. An organizational model of the process of increasing the development of management staff of the organization in a knowledge economy. This paper improved theoretical and methodological basis of the system of administrative personnel. In the context of globalization and integration of the domestic labor market, the managerial staff of the organization acts as a valuable socio-economic resource, the cost of professional qualities and competencies of which is steadily growing due to the acquisition of new knowledge by employees. The effectiveness of the managerial work of an organization, in contrast to the labor productivity of direct participants in the creation of material wealth, is not measured directly, but by the performance indicators of the work of business entities over a certain period of time. An important role in increasing the efficiency of the organization's managerial work belongs to the organization of labor of the employees of the management apparatus on a scientific basis, which means a system of sound technical, organizational and economic measures aimed at directly improving the organization and management methods using scientific and technical achievements, the widespread introduction of mechanization, automation and computerization of all functions of the management process.
Keywords: managerial staff; knowledge; knowledge economy; personnel development; increase of efficiency of development of managerial personnel of the organization in the conditions of knowledge economy